Molecular architecture and microporous structure of low mature lacustrine kerogen: A multi-parameter modeling of the Triassic Yanchang Formation, Ordos Basin - Yinhai Song; Meijun Li; Xiaoqiang Liu; Xia Luo; Qingyong Luo; Qingbin Xie; Haochen Chen; Zhihao Wang (Fuel, 2027)

Mitophagy-replenishment strategy targeting the aberrant endogenous dsDNA to enhance bone healing quality in the elderly - Zhengxia Ni; Yiyang Huang; Kun Xi; Jiannan Mao; Lingjun Wang; Jincheng Tang; Wenbo Wang; Xinzhao Jiang; Haochen Jiang; Liang Zhou; Jie Wu; Zhouye Ding; et al. (Chemical Engineering Journal, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

A numerical study of the possible influence of the ice nucleation process on the bolt-from-the-blue lightning production - Qianwei Zhao; Zheng Shi; Yanfeng Fan; Xuedong Cui; Haochen Chen; Wenzhong Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Recovery of silver and silicon from spent solar cells by direct separation driven by galvanic and chemical etching in molten chloride - Haochen Wang; Hongya Wang; Shiyu Wang; Yubo Zhou; Danfeng Wang; Fengyin Zhou; Xinyi Li; Junmin Peng; Xiang Chen; Dihua Wang; Huayi Yin (Science Bulletin, 2026)

Research on expansion of hydraulic fractures based on reservoir architecture: implications for well spacing in the northern Ordos Basin tight gas reservoir - Lei Bao; Qi Chen; Yuming Liu; Haochen Liu; Minghao Zhao; Xinqiang Liu; Jiagen Hou (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Insight into poplar fractionation enhancement via an eco-manufacturing process using sulfonated magnetic polystyrene solid acid and biphasic solvent - Haochen Du; Cuiyi Liang; Shijun Liu; Xuesong Tan; Yang Chen; Shiyou Xing; Yu Zhang; Wei Liu; Wen Wang; Xin Shi; Zhongming Wang; Wei Qi (Chemical Engineering Journal, 2026)

Climate change-driven propagation of meteorological-hydrological-groundwater drought: insights from the Pearl River Basin, China - Haochen Yuan; Xiuyu Liang; Jianli Chen; Haiyun Shi; Yong Tian; Chunmiao Zheng (Journal of Hydrology, 2026)

Comparative study of promising CaAl-LDH and conventional immobilizing agents in mitigating ecological and health risks associated with soil Pb contamination - Jianying Yu; Nan Wei; Haochen Fang; Yining Chen; Tengfei Guo; Qijia Zhang; Yangyang Chen; Jiahong Yu; Jianyu Zhang; Zeliang Han; Kaiqin Xu; Ching Yuan; et al. (Journal of Environmental Management, 2026)

Mechanobiological Response of Osteocyte TRPV4 Base on the Piezoelectricity of Bone Matrix - Shibo Gu; Yuqing Duanwang; Yinuo Zhao; Shuo Gao; Haochen Li; Xinrui Wu; Quanyou Zhang; Yanru Xue; Meng Zhang; Xiaogang Wu; Weiyi Chen (Annals of Biomedical Engineering, 2026)

High-temperature corrosion mechanism of ferritic stainless steel in steam-hydrogen atmosphere for solid oxide electrolysis cell based on reactive force field method - Enhua Wang; Yajing Zhang; Jingwen Mao; Haochen Dang; Minggao Ouyang; Haoran Hu; Hewu Wang; Yadi Liu; Youpeng Chen; Languang Lu; Dongsheng Ren (Fuel, 2026)

Spatial and seasonal variations of the phytoplankton community under multiple stressors in the area around Nan'ao Island, northern South China Sea - Zhixi Zhou; Yujiao Chen; Huijuan Tang; Guohong Xiao; Haochen Huang; Zhixin Ke (Continental Shelf Research, 2026)

Numerical study on flow characteristics, hydrodynamics, and structural response of an integrated aquaculture platform with WECs and wind turbine - Can Yang; An Hu; Haochen Zhang; Hailong Chen (Ocean Engineering, 2026)

A comparative study on the occurrence and pore structure characteristics of CH4 and CO2 hydrates in sandy sediments using SEM-EDS technology - Lujun Wang; Haochen Yang; Chuanqi Sun; Jianye Sun; Xiluo Hao; Chengfeng Li; Bin Zhu; Yunmin Chen (Gas Science and Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

SUMOylation in Mitochondrial Quality Control: Mechanisms and Implications for Neurodegenerative Disease - Qingya Wu; Dengying Fan; Jianhui Ren; Yafang Xing; Zhengzheng Chen; Haochen Jin; Yisheng Lu; Xiaopeng Wang; Hua Zheng (Molecular Neurobiology, 2026)

Nanoplastic-mediated disruption of freshwater carbon cycling via modulating of plankton communities - Peng Wang; Haochen Yang; Chengjing Li; Zihao Fu; Qianqian Xiang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Recent advances of high-intensity ultrasound on protein structure and quality: Allergenicity, physicochemical properties, functionality assessment and future perspective - Xiaowen Pi; Haochen Ye; Qingqing Cao; Yijia Jia; Yi Chen; Chunyan Bo; Bowen Li; Jinshen Chu (Food Chemistry, 2025)

Study on the microscopic mechanism and kinetics of nitrogen migration in the pyrolysis process of sewage sludge - Bin Chen; Haochen Shi; Yujie Zeng; Yuxuan Zhang (Journal of Water Process Engineering, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Long-term effects of short-term functional membrane covering on humification process and carbohydrate-active enzymes during dairy manure composting at industrial scale - Muqing Zhan; Ya Su; Qianting Zhuo; Sanwei Yang; Haochen Shao; Chen Fang (Journal of Environmental Chemical Engineering, 2025)

Impact of biochar on the fate of 15N-labelled fertilizer in water-saving and flooding irrigated rice-soil system under three different nitrogen sources - Xi Chen; Zhihui Wang; Ningbo Cui; Li Guo; Kangning Yu; Haochen Jin; Shikuan Sun (Plant and Soil, 2025)

Effects of nano-selenium addition on the nitrogen cycle during composting: Mechanistic regulation of denitrification and organic nitrogen metabolism - Zaiguang Hou; Xiaojiang Ma; Muqing Zhan; Haochen Shao; Qianting Zhuo; Xi Chen; Sanwei Yang; Chen Fang (Journal of Environmental Management, 2025)

Bimetallic Mn and Cr co-doped nickel cobalt phosphide nanoneedle arrays as bifunctional electro catalysts for overall water splitting - Yongyi Zhang; Mingyan Zhang; Haochen Zhang; Dan Han; Jinping Wang; Rui Yang; Chunling Zuo; Xiaoshuang Chen (Fuel, 2025)

Cigarette smoke-induced PPAR signaling dysregulation accelerates Alzheimer's disease pathogenesis and cognitive decline in 5xFAD mice - Yunqi Xie; Haochen Wang; Yajie Zhang; Bingbing Lin; Yuting Chen; Kai Li; Huanwen Tang; Qian Sun (Food and Chemical Toxicology, 2025)

Deep learning-based automatic cranial implant design through direct defect shape prediction and its comparison study - Afaque Rafique Memon; Haochen Shi; Tarique Rafique Memon; Jan Egger; Xiaojun Chen (Medical & Biological Engineering & Computing, 2025)

Effect of semi-permeable membrane coverage on carbon dioxide emissions during composting: Insights into carbon metabolism pathways, dominated by the tricarboxylic acid cycle - Chen Fang; Qian Lv; Haochen Shao; Muqing Zhan; Xi Chen; Sanwei Yang (Journal of Environmental Management, 2025)

Rational design of paclitaxel prodrugs for facile preparation of in-situ therapeutic system in antitumor applications - Lanqing Wang; Zhaofan Yang; Guanyu Jin; Bingzheng Yu; Wei Zhang; Xuesi Chen; Haochen Yao; Cuiping Yao; Shixian Lv (Chemical Engineering Journal, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Silver nanoparticles alter plankton-mediated carbon cycle processes in freshwater mesocosms - Peng Wang; Qianqian Xiang; Zihao Fu; Chengjing Li; Haochen Yang; Jun Zhang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Crystalline carbon nitride derived self-assembly composite membranes with enhanced self-cleaning performance toward dye/salt separation - Yujing Qiu; Haochen Xu; Ying Zhou; Beizhao Chen; Zhongying Wang; Yi Yang; Qile Fang; Ying Mei (Journal of Environmental Management, 2025)

Adsorption kinetics of different mercury species on three kinds of micro-/nano-plastics in micro-polluted aquatic environments and their combined toxicity - Siqi Wu; Chen Yang; Haochen Xu; Yiwei Zhu; FengFu Fu; Yue Lin (Science of The Total Environment, 2025)

Ocean mixed layer depth 2000–2020: Estimation assessment and long-term trends - Haochen Tang; Chen Wang; Huimin Li; Yijun He (Progress in Oceanography, 2025)

Mechanism of reducing antibiotic resistance genes by nano-selenium during composting: insight into host microorganisms and a two-component system - Xi Chen; Muqing Zhan; Haochen Shao; Shuangshuang Ma; Li Liu; Zuyong Chen; Chen Fang (Journal of Environmental Management, 2025)

Exposure risk and fate of antibiotic resistance genes during industrial-scale composting of dairy manure in a short-term micro-positive pressure environment - Chen Fang; Muqing Zhan; Pingfan Wu; Haochen Shao; Sanwei Yang; Xuefeng Wen; Guangqun Huang (Journal of Environmental Chemical Engineering, 2025)

Ultra-low Pt induced amorphous/crystalline heterophase Pt-Co2P hollow nanotubes for superior water electrolysis at industrial temperatures - Ziting Li; Peng Zhou; Mingyan Zhang; Haochen Zhang; Yongyi Zhang; Dan Han; Xiaoshuang Chen (Fuel, 2025)

Facility of tomato plant organ segmentation and phenotypic trait extraction via deep learning - Jiangjun Yao; Yan Gong; Zhengyan Xia; Pengcheng Nie; Honggang Xu; Haochen Zhang; Yufei Chen; Xuehan Li; Zhe Li; Yiming Li (Computers and Electronics in Agriculture, 2025)

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Differential impacts of microplastics on carbon and nitrogen cycling in plant-soil systems: A meta-analysis - Yige Liu; Siyi Chen; Pengyu Zhou; Haochen Li; Quan Wan; Ying Lu; Bo Li (Science of The Total Environment, 2024)

Challenges for sustainable development goal of land degradation neutrality in drylands: Evidence from the Northern Slope of the Tianshan Mountains, China - Haochen Yu; Dengyu Yin; Bin Yang; Yongjun Yang; Fu Chen (Science of The Total Environment, 2024)

Exploring the ecological meanings of temperature sensitivity of ecosystem respiration from different methods - Yang Zhang; Gaofeng Zhu; Kun Zhang; Heng Huang; Liyang He; Cong Xu; Huiling Chen; Yonghong Su; Yuzhong Zhang; Haochen Fan; Boyuan Wang (Science of The Total Environment, 2024)

Energy partitioning over an irrigated vineyard in arid northwest China: Variation characteristics, influence degree, and path of influencing factors - Huiling Chen; Yongtai Zhu; Gaofeng Zhu; Yang Zhang; Liyang He; Cong Xu; Kun Zhang; Jing Wang; Ramamoorthy Ayyamperumal; Haochen Fan; Boyuan Wang (Agricultural and Forest Meteorology, 2024)

The pyrolysis of 4,4,8,10-tetramethyl decalin and the influence of molecular structures on oil thermal cracking: A ReaxFF molecular dynamics simulation and DFT study - Haochen Chen; Meijun Li; Xiaoqiang Liu; Qiuya Han; Wenke Li; Siyuan Zhang (Fuel, 2024)

Effects of distinct lipid phases and packaging on alleviating the quality deterioration of surimi gels during frozen storage - Yuxin Wang; Xidong Jiao; Nana Zhang; Bowen Yan; Haochen Ding; Weijian Ye; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

Trophic relationship between mussels and scale worms under various seepage intensities in the haima cold seep: Insights from stable isotopes (δ13C and δ15N) and C:N:P stoichiometry - Zhixin Ke; Haochen Huang; Danting Chen; Yehui Tan (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Insights into the complementation potential of the extreme acidophile’s orthologue in replacing Escherichia coli hfq gene—particularly in bacterial resistance to environmental stress - Wenbo Hu; Xingyu Huo; Haochen Bai; Zongling Chen; Jianxin Zhang; Hailin Yang; Shoushuai Feng (World Journal of Microbiology and Biotechnology, 2024)

Engineering mesoporous nascent MnO2 colloids for efficient elimination of emerging organic contaminants - Zhuoyue Liu; Dong Cheng; Haochen Yin; Jianghao Zhao; Jiale Zhang; Rongzhi Chen; Shengjiong Yang; Jing Wei; Gen Wang (Journal of Water Process Engineering, 2024)

Thawing of goose meat by simultaneous dual frequency ultrasound for process efficiency: Thawing rate, quality attributes, structural characteristics - Wangbin Shi; Yang Wang; Xingyu Chen; Haochen Hu; Xi Chen; Benjamin Kumah Mintah; Mokhtar Dabbour; Xiangren Meng; Zhaoli Zhang; Ronghai He; Haile Ma (Innovative Food Science & Emerging Technologies, 2024)

A new ternary diagram to decipher the evolution of maturity and biodegradation of crude oil using ESI FT-ICR MS - Dongyong Wang; Meijun Li; Jianfa Chen; Haochen Chen; Quan Shi (Fuel, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

An artificial neural network-based machine learning approach to correct coarse-mesh-induced error in computational fluid dynamics modeling of cell culture bioreactor - Fernando José Cantarero-Rivera; Ran Yang; Haochen Li; Hairong Qi; Jiajia Chen (Food and Bioproducts Processing, 2024)

The biological source and paleoenvironment implication of rare short-chain lanostanes in alkaline lacustrine sediments - Dongyong Wang; Meijun Li; Jianfa Chen; Hong Xiao; Xianli Zou; Lu Yang; Haochen Chen; Huiqiang Qin (Organic Geochemistry, 2023)

Recognition of airfoil wake structure based on deep learning - Haibao Hu; Xiangbo Du; Haochen Lu; Xiaopeng Chen; Peng Du (Ocean Engineering, 2023)

Multiscale analysis framework for assessing land degradation neutrality with ecosystem services: A case study of the Yellow River basin - Haochen Yu; Dengyu Yin; Jian Zhang; Peng Yu; Fu Chen (Journal of Cleaner Production, 2023)

Capturing urban recreational hotspots from GPS data: A new framework in the lens of spatial heterogeneity - Haochen Shi; Hao Huang; Ding Ma; Lu Chen; Miaoxi Zhao (Computers, Environment and Urban Systems, 2023)

Soil Salinity Estimation Over Coastal Wetlands Based on Random Forest Algorithm and Hydrological Connectivity Metric - Haochen Sui; Dawei Chen; Jiaguo Yan; Bin Li; Wei Li; Baoshan Cui (Frontiers in Marine Science, 2022)
Owing to climate warming and human activities (irrigation and reservoirs), sea level rise and runoff reduction have been threatening the coastal ecosystem by increasing the soil salinity. However, short-term sparse in situ observations limit the study on the response of coastal soil salinity to external stressors and thus its effect on coastal ecosystem. In this study, based on hydrological connectivity metric and random forest algorithm (RF), we develop a coastal soil salinity inversion model with in situ observations and satellite-based datasets. Using Landsat images and ancillary as input variables, we produce a 30-m monthly grid dataset of surface soil salinity over the Yellow River Delta. Based on the cross-validation result with in situ observations, the proposed RF model performs higher accuracy and stability with determination coefficient of 0.89, root mean square error of 1.48 g·kg -1 , and mean absolute error of 1.05 g·kg -1 . The proposed RF model can gain the accuracy improvements of about 11–43% over previous models at different conditions. The spatial distribution and seasonal variabilities of soil salinity is sensitive to the changing signals of runoff, tide, and local precipitation. Combining spatiotemporal collaborative information with the hydrological connectivity metric, we found that the proposed RF model can accurately estimate surface soil salinity, especially in natural reserved regions. The modeling results of surface soil salinity can be significant for exploring the effect of seawater intrusion and runoff reduction to the evolution of coastal salt marsh ecosystems.

Machine Learning-based Weather Support for the 2022 Winter Olympics - Jiangjiang Xia; Haochen Li; Yanyan Kang; Chen Yu; Lei Ji; Lve Wu; Xiao Lou; Guangxiang Zhu; Zaiwen Wang; Zhongwei Yan; Lizhi Wang; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2020)

Reclamation of desert land to continuous cotton cropping affects soil properties and microbial communities in the desert-oasis ecotone of Xinjiang, China - Jinbiao Li; Guangming Liu; Jin-Hyeob Kwak; Scott X. Chang; Haochen Gao; Qicong Wu; Jingsong Yang; Jinlin Chen (Journal of Soils and Sediments, 2020)

A Model Output Machine Learning Method for Grid Temperature Forecasts in the Beijing Area - Haochen Li; Chen Yu; Jiangjiang Xia; Yingchun Wang; Jiang Zhu; Pingwen Zhang (Advances in Atmospheric Sciences, 2019)